Multidecadal variability and climate shift in the North Atlantic Ocean. Issue 10 (21st May 2017) - Seidov, Dan; Mishonov, Alexey; Reagan, James; Parsons, Rost
Abstract: Decadal variability of ocean heat content (OHC) and temperature trends over 60 years in the North Atlantic Ocean were analyzed using a new high‐resolution ocean climatology based on quality‐controlled historic in situ observations. Тwo 30 year ocean climates of 1955–1984 and 1985–2012 were compared to evaluate the climate shift in this region. The spatial distribution of the OHC climate shift is highly inhomogeneous, with the climate shift being the strongest southeast of the Gulf Stream Extension. This may be caused by the Atlantic Meridional Overturning Circulation slowdown in conjunction with heaving of warm subtropical water. The 30 year climate shift shows higher OHC gain in the Gulf Stream region than reported in shorter timescale estimates. The OHC change is generally coherent with the Atlantic Multidecadal Oscillation index. This coherence suggests that quasi‐cyclicity of the OHC may exist, with a period of 60 to 80 years, superimposed on the slow basin‐wide warming trend. Key Points: Spatial distribution of the climatic shift of ocean heat content is highly inhomogeneous in the North Atlantic Ocean Decadal ocean climate variability mostly matches that of the Atlantic Multidecadal Oscillation index Strong subsurface warming in the Gulf Stream area can be partially due to heaving of the 18° water